Sensitivitas Bakteri Gram Negatif yang Diisolasi dari Kaki Kecoa (Periplaneta americana)di Area Rumah Sakit dan Perumahan di Kota Palu terhadapBeberapa Antibiotik - I Nengah Kundera; Mursito Bialangi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Cockroaches (Periplaneta americana) are often found in homes, restaurants, hotels, hospitals, warehouses, offices, libraries, and others. The existence of these highly dynamic animals is suspected of causing nosocomial infections at the hospitals and acting as vectors and hosts associated with bacteria carried on its feet. This research aims to analyze the sensitivity of Gram-negative bacteria isolated from Cockroach feet in the hospital and residential areas in Palu City against some antibiotics. This research is an explorative laboratory experiment research, with the method of bacteria identification, isolation and antibiotic test using standard procedure "The Bauer-Kirby". The results of bacterial identification in three areas of the Palu Hospital are Klebsiella ozaenaeSalmoella arizonae, Salmonella sp. Escherichia coli, Salmonella cholerae-suis and Salmonella simultans, while the bacteria from the residential area, Escherichia coli, Klebsiellapneumoniae, Proteus vulgaris, Salmonella arizonae, and Proteus mirabilis. The results of bacterial sensitivity tests on five antibiotics showed that all of these bacteria were resistant to the antibiotics of Vancomycin, Chloramphenicol, and Amoxycillin, but were still sensitive to Ciprofloxacin and Ofloxacin.